MDA levels in the pancreas, testes, liver, and plasma of diabetic rats: The effect of snakehead (Channa striata) extract - NURLITA ABDULGANI; DEWI HIDAYATI; RESSY ADINOVITASARY; VARAH OLIVIATIE; AYU DIAH SEKARTAJI (Smujo International, 2020)
Abstract. Abdulgani N, Hidayati D, Adinovitasary R, Oliviatie V, Sekartaji AD. 2020. MDA levels in the pancreas, testes, liver, and plasma of diabetic rats: The effect of snakehead (Channa striata) extract. Nusantara Bioscience 12: 50-54. There are several biomarkers of oxidative stress in diabetes mellitus; one of those biomarkers is Malondialdehyde (MDA). Increasing oxidative stress will cause increased tissue damage. This study was conducted to determine the effect of snakehead extract (SHE) on MDA level of pancreas, testes, liver, and plasma of alloxan-induced diabetic rats. There were 5 groups of treatments: non-diabetic rats/negative control (C-), diabetic rats/positive control (C+), and 3 SHE level of administration: 1 mL/day (low dose/LD), 1.6 mL/day (middle dose/MD) and 2.1 mL/day (high dose/HD). Alloxan-induced diabetic rats were administered with SHE extract orally every day for two weeks. The results showed that MDA levels in the testes, liver, pancreas, and plasma of diabetic rats administered with SHE and non-diabetic rats/negative controls (C-) were significantly lower (p <0.05) compared to MDA levels in the testes, liver, pancreas, and plasma of diabetic rats without SHE administration (positive control/ C +). The highest dose of SHE treatment (2.1 mL/day) results in decreasing MDA levels were not significantly different (p> 0.05) with the group of non-diabetic rats / negative controls (C-). The conclusion of this study was increasing SHE administration up to 2.1 mL/day result in reducing more of MDA levels in plasma, pancreas, liver, and testes of diabetic rats.